A Content Analysis on Thesis About Organizational Identification - Yigit, Burcu (BC GRUP INC, 2017)
The aim of this study is to evaluate the open access thesis on organizational identification that are published in Turkish Higher Education National Thesis Center according to publication years, university names, institutes, departments, sample sizes, application area of the study, subjects. It was reached totally 50 thesis. Based on the screening model, the data was analyzed by the content analysis method. As a result of the study, the concept of organizational identification is seen intensely in 2015. Gazi University and Marmara University are the leading universities that published thesis about organizational identification. According to institutes, thesis were published mostly in the Institute of Social Sciences in business administration/management&organization department. The range of sample size changes from 1 to 250. As an application area of the study, mainly private sector employees were included to the study. Organizational trust, leadership and organizational justice are mostly preferred studies.
Keywords: Organizational Identification; Identification; Content Analysis; Business & Economics; Social Issues